War Budget, 1939 (1939)
1939 1939-1945 "War Budget, 1939" [HFR0206], 1939 The government had voted an additional £500 million pounds for armaments in the 1939 War Budget. This cartoon from Labour Research, published by the Labour Research Department, was concerned that money would be raised by an attack on the wages and living standards of the working class.